Some Characteristics of Cross-Linked Hidroxypropyl Sago Starch - Haryadi Haryadi; Kapti Rahayu Kuswanto (agriTECH, 1996)
Sago starch was laboratory hydroxypropylated using 1% propylene oxide in alkaline condition, then cross-linked using 9.000 - 0.025 % phosphorus oxychloride. The dual modified starches with level of cross-linking ranging from 0.0000 to 0.0186 were characterized for amylographic properties, swelling power, paste turbidity, and in vitro digestibility using porcine pancreatic a-amylase. The cross-linking procedure applied to dual modification nearly unchanged the pasting temperature, i. e. at 62.5°C. Cross-linked, hydroxypropyl starches with DS more than 0.0150 had similar amylographic properties which showed high heat and shear stability of the paste. Cross-linking resulted in decrease in the swelling power and the in vitro digestibility of the starch. Hydroxypropylationprior to subsequent modification facilitate the cross-linking with a consequence of lower pasting temperature, higher maximum viscosity, higher swelling power, and lower digestibility.